La situation de la langue ossète en Ossétie du Sud et le rôle des conflits de 1920, 1991-1992 et 2008 - Laurent Alibert (Lengas)
We choose here to study the evolution of Ossetic situation in South Ossetia through the three last armed conflicts with Georgia and during the USSR period. The study will start from a contradiction: during the « five days war » of august 2008, whereas international media presented frequently South Ossetia as a russian-speaking area, the Ossetic language (non-slavic language, last remnant of the east-iranian group) was daily spoken by the population (and significantly more than in North Ossetia) and was still the basis of collective consciousness. The abolition of an official status for Ossetic language (which was co-official with Russian and Georgian on the territory of the oblast during the soviet period) during the Gamsakhurdia period (first georgian government post-USSR) was, for Ossetian people one of the two main reasons for choosing independence – the other one being the territorial denial of South Ossetia (in Ossetic « Hussar Iryston ») and of its history in favor of the Georgian conception of the territory as Samachablo, a part of Shida Kartli. We will study some socio-linguistic issues during the three last armed conflicts and between them (consequences of population movements, attack on the institutional recognition of the language, diglossia and so on).